Persistent functional loss following ruptured Achilles tendon is associated with reduced gastrocnemius muscle fascicle length, elongated gastrocnemius and soleus tendon, and reduced muscle cross‐sectional area. Issue 6 (24th August 2019) - Svensson, René B.; Couppé, Christian; Agergaard, Anne‐Sofie; Ohrhammar Josefsen, Christian; Jensen, Mikkel Holm; Barfod, Kristoffer Weisskirchner; Nybing, Janus D.; Hansen, Philip; Krogsgaard, Michael; Magnusson, S. Peter
Abstract: We examined muscle function, muscle architecture, and tendon length bilaterally in persons who experience a functional deficit 2 years after an Achilles tendon rupture. Eleven persons were investigated on the injured compared with the uninjured side 47 ± 7 months (mean ± SD) after a tendon rupture. Heel‐rise data, plantar flexion strength, tendon resting angle 3D MRI‐determined tendon length and muscle cross‐sectional area, ultrasound‐determined fascicle length, and pennation angle were obtained. The heel‐rise test yielded reduced max height (32%), number of repetitions (54%), and work performed (61%), P  < .001. Plantar flexion strength was impaired ( P  < .001) with the knee in extension (20%‐42%) and flexion (29%‐39%). Muscle cross‐sectional area was reduced for both the soleus (36%) and gastrocnemius muscles (46%; P  < .001). Both the soleus tendon (55%) and the gastrocnemius tendon (14%) were longer ( P  < .001), and the fascicle length of the medial gastrocnemius was substantially reduced (18%; P  < .001). The difference in heel‐rise height correlated to that of the gastrocnemius tendon elongation, r  = .66, P  < .05, but not soleus tendon elongation. These data show that a functional deficit after an Achilles tendon rupture is associated with an elongated soleus and gastrocnemius tendon along with a reduced soleus and gastrocnemius muscle cross‐sectional area and gastrocnemius fascicle length.